2016
DOI: 10.1063/1.4939558
|View full text |Cite
|
Sign up to set email alerts
|

Crystal and magnetic structures of Cr1∕3NbSe2 from neutron diffraction

Abstract: Neutron diffraction measurements of the Cr intercalated niobium diselenide Cr 1=3 NbSe 2 together with magnetization measurements have revealed that this compound exhibits ferromagnetic ordering below T C ¼ 96 K unlike a chiral helimagnetic order observed in the sulfide compound Cr 1=3 NbS 2 . As derived from neutron diffraction data, the Cr magnetic moments l Cr ¼ 2.83 6 0.03 l B in Cr 1=3 NbSe 2 are aligned within basal plane. The discrepancy in the magnetic states of Cr 1=3 NbS 2 and Cr 1=3 NbSe 2 is ascrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…In the present study, most crystals grown with x > 1 reveals the CSL behavior, while a particular crystal with x = 1.020 (3) shows the ferromagnetic response. This exception may be caused by disorders on the Cr sites, the presence of which can be probed by single crystal Xray diffraction measurements, as observed in a ferromagnetic CrNb 3 Se 6 41 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, most crystals grown with x > 1 reveals the CSL behavior, while a particular crystal with x = 1.020 (3) shows the ferromagnetic response. This exception may be caused by disorders on the Cr sites, the presence of which can be probed by single crystal Xray diffraction measurements, as observed in a ferromagnetic CrNb 3 Se 6 41 .…”
Section: Discussionmentioning
confidence: 99%
“…However, there are reports 19,22 that the Cr ions take the positions of not only 2c, but also 2b (0, 0, 0) and 2d (2/3, 1/3, 1/4). In the case of CrNb 3 Se 6 , which has the same structure as that of CrNb 3 S 6 , only 5 percent of Cr occupy Wyckoff 2c position, but 90 percent occupy Wyckoff 2b (0, 0, 0) position 41 . Resultantly, the magnetic structure is not CHM, but ferromagnetic one.…”
Section: Crystal Structurementioning
confidence: 99%
“…SuperHRPD is expected to (1) detect tiny distortions never detected before in the field of strongly correlated systems, multiferroics, magnetic materials; (2) facilitate high-precision structural analysis of energy materials; (3) develop structure science of hybrid materials, supermolecules, and pharmaceuticals. Various achievements have been made in many fields by the user program and the instrumental group project that commenced in December 2008 [73][74][75][76][77][78][79][80].…”
Section: Super High-resolution Powder Diffractometer Superhrpdmentioning
confidence: 99%
“…A powder diffraction study on M x NbSe 2 ( M = V, Cr, Mn, Fe, Co, and Ni) has shown the appearance of weak reflection corresponding to an ordered structure with 2 a o × 2 a o super-lattice above 25% intercalation . Cr 0.33 NbSe 2 has been studied using a neutron diffraction study; however, no clear evidence of structural ordering was observed . STM and AFM study on Fe 0.33 NbSe 2 has shown 2 a o × 2 a o × 1 c 0 super-lattice formation in this compound .…”
Section: Introductionmentioning
confidence: 99%